INFLUENCE OF QUALITY OF WORK LIFE, PERCEIVED UNION EFFECTIVENESS AND JOB SECURITY ON UNION COMMITMENT AMONG BANK EMPLOYEES - Abdul Halim Bin Abdul Majid; Nalini Thamotharan; Noor Asma Jamaluddin (Management Study Program, Faculty of Business and Economics, Petra Christian University, 2021)
This study investigates the relationship between quality of work-life, perceived union effectiveness and job security with union commitment among bank employees in Malaysia. This study is motivated by the decline of union density worldwide in recent times. Indeed, the National Union of Bank Employees (NUBE) has experienced a huge decline of membership, which may weaken and challenge the union to perform efficiently. Hence, this study examined the influence of quality of work-life, perceived union effectiveness and job security on union commitment. Survey questionnaires were distributed using simple random sampling to all five branches of the NUBE in Malaysia. The primary data were collected from 350 respondents and analyzed using correlation and multiple regression analysis. The findings of the study indicated that quality of work-life and perceived union effectiveness have positive and significant influences on union commitment. On the other hand, job security showed no significant influence on union commitment. Thus, representatives or the leaders in NUBE should focus more on the job insecurity of member in banking sector and should encourage the younger generation to participate in the union activities. Membership declining dilemma can be resolved by giving priorities to important issue such as job security among banking employees.